Heterosis extends the reproductive ability in aged female mice†. Issue 4 (18th December 2018) - Ozawa, Yusuke; Watanabe, Kenji; Toda, Toshihiko; Shibuya, Shuichi; Okumura, Nobuaki; Okamoto, Naoki; Sato, Yorino; Kawashima, Ikko; Kawamura, Kazuhiro; Shimizu, Takahiko
Abstract: Heterosis is the beneficial effect of genetical heterogeneity in animals and plants. Although heterosis induces changes in the cells and individual abilities, few reports have described the effect of heterosis on the female reproductive ability during aging. In this study, we investigated the reproductive capability of genetically heterogeneous (HET) mice established by the four-way crossing of C57BL/6N, BALB/c, C3H/He, and DBA/2. We found the HET females naturally and repeatedly produced offspring, even in old age (14–18 months of age). We also found that HET females showed a significantly enlarged body and organ sizes in both youth and old age. In histological analyses, the numbers of primordial follicles, primary follicles, secondary follicles, and corpora lutea were significantly increased in the old ovaries of HET females compared with those in inbred C57BL/6 mice of the same age. In vitro fertilization experiments revealed that aged HET oocytes showed identical rates of fertilization, early development, and birth compared to those of young and old C57BL/6 oocytes. We further found the significantly increased expression of sirtuin genes concomitant with the up-regulation of R-spondin2 in old HET ovaries. These results confirm the novel phenotype, characterized by fertility extension and follicular retention due to heterosis, in old HET females. The HET female will be a valuable model for clarifying the mechanism underlying the effect of heterosis in the field of reproduction.